Conservación de la vitalidad pulpar en piezas autotransplantadas - Pineda Mejia, Martha Elena (2002)
To carry out this investigation, eight patients 15 to 21 years old of Central Clinic of UNMSM Dentistry Faculty who had the indication for. first permanent molar extraction and at the same time had a third molar germ in eruption, were selected. The germ was at least in a Nolla development stage 7, 8 ó 9. Having the patient´s respective consent they underwent the autotransplantation of the germ to the socket of the first molar within the same quadrant. Cases were followed for a 12 weeks period. DIfferent tests to determine J the donor tooth was vital or not, were done. Six weeks after transplantation a high percentage of teeth began to respond to thermal and electric pu1p tests, the mobility they initially presented diminishing gradually. Until the time lapsed, the transplanted teeth clinically appeared to become firmer and conserved their pulp vitality. Being 70 to 80% of teeth that make it between the 6' and 8" week, increasing the percentage to 95% in an observation period of 12 " week. Iboth autotransplantation probed to be a simple technique, with acceptable percentages of success, coming to salve the loss of a 1 permanent molar.